Toward unraveling reading–related modulations of tDCS–induced neuroplasticity in the human visual cortex - Antal, Andrea; Ambrus, Géza Gergely; Chaieb, Leila (Frontiers in Psychology, 2014)
Stimulation using weak electrical direct currents has shown to be capable of inducing polarity dependent diminutions or elevations in motor and visual cortical excitability. The aim of the present study was to test if reading during transcranial direct current stimulation (tDCS) is able to modify stimulation-induced plasticity in the visual cortex. Phosphene thresholds (PT) in 12 healthy subjects were recorded before and after 10 minutes of anodal, cathodal and sham tDCS in combination with reading. Reading alone decreased PTs significantly, compared to the sham tDCS condition without reading. Interestingly, after both anodal and cathodal stimulation there was a tendency toward smaller PTs. Our results support the observation that tDCS-induced plasticity is highly dependent on the cognitive state of the subject during stimulation, not only in the case of motor cortex but also in the case of visual cortex stimulation.